COVID-19 and the mental health of physical education students before and during lockdown - Mouloud; Nawal (VIREF Revista de Educación Física, 2020)
Objective: to analyze the mental health of physical education students before and during lockdown. Method: a descriptive study was cconducted. The Mental Health Scale was employed to assess mental health of physical education students. An online survey was fulfilled by 103 students of the Institute of Physical Education and Sport, University of Ouargla, in Algeria. Results: the results showed that there were statistically significant differences in mental health among physical education students before and during lockdown. There were no statistically significant differences in mental health among students before and during the lockdown period, depending on the academic level variable, and there were statistically significant differences in mental health among students before and during the lockdown period, depending on the city variable. Conclusion: establishing online mental health platforms and programs is necessary.